2019
DOI: 10.1371/journal.pone.0213223
|View full text |Cite
|
Sign up to set email alerts
|

Can early assessment of hand grip strength in older hip fracture patients predict functional outcome?

Abstract: Decreased muscle strength is not only a risk factor for hip fracture in older patients, but plays a role in recovery of physical function. Our aim was to assess the role of grip strength measured early after hip fracture, and classified according to the EWGSOP2 criteria in predicting short- and long-term functional recovery. One hundred ninety-one patients with acute hip fracture consecutively admitted to an orthopaedic hospital have been selected. A multidimensional geriatric assessment evaluating sociodemogr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 34 publications
7
46
0
3
Order By: Relevance
“…Our study further corroborated previous ndings [16,[18][19][20] about the patient characteristics associated with low GS in this population undergoing primary THA. As expected, there were signi cant differences in preoperative characteristics between the low GS and normal GS cohorts.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study further corroborated previous ndings [16,[18][19][20] about the patient characteristics associated with low GS in this population undergoing primary THA. As expected, there were signi cant differences in preoperative characteristics between the low GS and normal GS cohorts.…”
Section: Discussionsupporting
confidence: 92%
“…A number of previous studies have examined the predictive role of low GS for the clinical outcomes following orthopedic surgery [15][16][17][18][19]. For instance, Shen et al reported patients with high preoperative GS…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is of great significance to provide early rehabilitation training for patients with lower limb dyspraxia. 3,4 Several studies have reported a limited number of factors, such as pain, anxiety and low life quality that are caused by surgery associated with functional recovery. 5,6 Elderly patients are often accompanied by hypertension, osteoporosis and other health problems, which lead to slow wound healing following surgery.…”
Section: Introductionmentioning
confidence: 99%